Profiling Eco-literacy in Elementary School Students: A Qualitative Case Study Approach - Najib, Muhamad Ainun; Nurdiani, Sulastri; Puspaningtyas, Anindya; Anjani, Siti Ratna; Setiawan, Raysa Amaviska Putri; Maharani, Arista Selly; Ningsih, Rizki Wulan; Putri, Amanda Sabrina Zahra; Marliani, Hetty; Fajari, Laksmi Evasufi Widi (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2024)
This study aims to describe the eco-literacy profile formulated by the Centre of Eco-literacy. The research design used in this article is qualitative with a case study approach. The research subjects consist of 5 students, two teachers, and the principal. The data collection techniques in this study used three techniques: observation, interviews, and documentation. The data analysis technique examines the data obtained from the beginning of data collection to conclude. The research result shows that: (1) in the cognitive aspect, students understand environmental issues and can connect this knowledge with concrete actions in their daily lives; (2) the emotional aspect shows that students are deeply aware of the interdependence between living beings and the environment, accompanied by empathy and care for nature; (3) the activity aspect is evident from students' involvement in using tools and resources wisely and integrating eco-literacy principles into various practical activities; and (4) the spirit aspect is reflected in the increased awareness of students regarding the relationship between humans and nature, manifested through actual actions born from their knowledge and care. This study concludes that students' eco-literacy profile is good, with skills encompassing cognitive, emotional, activity, and spirit aspects that mutually support understanding and responding to environmental issues effectively. This research is expected to serve as a reference for policymakers and schools in implementing eco-literacy in elementary schools.